Functional, Antigen-Specific Stem Cell Memory (TSCM) CD4+ T Cells Are Induced by Human Mycobacterium tuberculosis Infection - Mpande, Cheleka A. M.; Dintwe, One B.; Musvosvi, Munyaradzi; Mabwe, Simbarashe; Bilek, Nicole; Hatherill, Mark; Nemes, Elisa; Scriba, Thomas J.; , The SATVI Clinical Immunology Team; Ontong, Cynthia; Filander, Elizabeth; Alexander, Fadia; et al. (Frontiers in Immunology, 2018)
Background Maintenance of long-lasting immunity is thought to depend on stem cell memory T cells (TSCM), which have superior self-renewing capacity, longevity and proliferative potential compared with central memory (TCM) or effector (TEFF) T cells. Our knowledge of TSCM derives primarily from studies of virus-specific CD8+ TSCM. We aimed to determine if infection with Mycobacterium tuberculosis (M. tb), the etiological agent of tuberculosis, generates antigen-specific CD4+ TSCM and to characterize their functional ontology. Methods We studied T cell responses to natural M. tb infection in a longitudinal adolescent cohort of recent QuantiFERON-TB Gold (QFT) converters and three cross-sectional QFT+ adult cohorts; and to bacillus Calmette–Guerin (BCG) vaccination in infants. M. tb and/or BCG-specific CD4 T cells were detected by flow cytometry using major histocompatibility complex class II tetramers bearing Ag85, CFP-10, or ESAT-6 peptides, or by intracellular cytokine staining. Transcriptomic analyses of M. tb-specific tetramer+ CD4+ TSCM (CD45RA+ CCR7+ CD27+) were performed by microfluidic qRT-PCR, and functional and phenotypic characteristics were confirmed by measuring expression of chemokine receptors, cytotoxic molecules and cytokines using flow cytometry. Results M. tb-specific TSCM were not detected in QFT-negative persons. After QFT conversion frequencies of TSCM increased to measurable levels and remained detectable thereafter, suggesting that primary M. tb infection induces TSCM cells. Gene expression (GE) profiling of tetramer+ TSCM showed that these cells were distinct from bulk CD4+ naïve T cells (TN) and shared features of bulk TSCM and M. tb-specific tetramer+ TCM and TEFF cells. These TSCM were predominantly CD95+ and CXCR3+, markers typical of CD8+ TSCM. Tetramer+ TSCM expressed significantly higher protein levels of CCR5, CCR6, CXCR3, granzyme A, granzyme K, and granulysin than bulk TN and TSCM cells. M. tb-specific TSCM were also functional, producing IL-2, IFN-γ, and TNF-α upon antigen stimulation, and their frequencies correlated positively with long-term BCG-specific CD4+ T cell proliferative potential after infant vaccination. Conclusion Human infection with M. tb induced distinct, antigen-specific CD4+ TSCM cells endowed with effector functions, including expression of cytotoxic molecules and Th1 cytokines, and displayed chemokine receptor profiles consistent with memory Th1/17 cells. Induction of CD4+ TSCM should be considered for vaccination approaches that aim to generate long-lived memory T cells against M. tb.